Midnight snacks are murder - Klein, Libby (Mystery author) (Klein, Libby (Mystery author) Poppy McAllister mystery., 2018)
Between trying to get her gluten-free baking business off the ground and helping her aunt remodel her old Victorian into the Butterfly House Bed and Breakfast in Cape May, New Jersey, Poppy is ready to call, “Mayday!” And now Aunt Ginny<U+2014>who's a handful wide-awake<U+2014>is sleepwalking on her new sleeping pill prescription and helping herself to neighbors<U+2019> snacks and knickknacks. Even more alarming, a local humanitarian who worked with troubled teens is found murdered, and the police suspect the “Snack Bandit.” Other than a bad case of midnight munchies and some mild knickknack kleptomania, Aunt Ginny is harmless. Someone<U+2019>s trying to frame her. Poppy will need to work tirelessly to uncover the killer and put the case to rest<U+2014>before Aunt Ginny has to trade in her B & B for a bunk bed behind bars . . .